2007
DOI: 10.1111/j.1365-2265.2007.02916.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of endothelium‐dependent flow‐mediated vasodilation in hyperthyroidism

Abstract: Summary Objective   Vascular responsiveness changes in hyperthyroid patients remains controversial. This study attempts to determine whether the vasomotor activity can be influenced by hyperthyroid conditions, and, if so, whether changes induced by hyperthyroidism may be restored to normal during the euthyroid state after treatment. Design   A case‐control clinical study. Patients and measurements   Forty‐five pretreated hyperthyroid patients (mean age 36·62 ± 10·12 years, 36 female) were compared with 45 gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…[18] However, another study demonstrated that flow-mediated endothelium-dependent vasodilation, as assessed by a noninvasive determinant of brachial FMD, increased in hyperthyroid patients. [19] This differences may be explained by the difference between subclinical and overt hyperthyroid condition. All the patients in that study were endogenous hyperthyroidism, and this was another dissimilarity between two studies.…”
Section: Discussionmentioning
confidence: 99%
“…[18] However, another study demonstrated that flow-mediated endothelium-dependent vasodilation, as assessed by a noninvasive determinant of brachial FMD, increased in hyperthyroid patients. [19] This differences may be explained by the difference between subclinical and overt hyperthyroid condition. All the patients in that study were endogenous hyperthyroidism, and this was another dissimilarity between two studies.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of coronary vasospasm owing to thyroid dysfunction has not yet been defined, but it is hypothesized that it might be associated with increased sensitivity to coronary artery vasoconstriction and decreased vasodilation. In addition, hyperthyroidism increases vasomotor activity, which has been demonstrated by increased endothelium-dependent flow-mediated vasodilation [ 9 ]. Interestingly, because thyroxine’s effect on peripheral circulation is vasodilation, it seems paradoxical that coronary artery vasospasm can be caused by hyperthyroidism although the coronary artery differs from peripheral vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of patients with VA have shown that high blood pressure and dyslipidemia, which are the traditional risk factors of atherosclerotic cardiovascular disease, are not significantly associated with vasospasm, but smoking is the only proven risk of vasospasm [ 5 , 6 ]. A recent study demonstrated that hyperthyroidism is associated with increased risk of developing myocardial infarction and stroke independent of atherosclerotic risk factors, but is not associated with mortality in a large scale cohort [ 7 ] Hyperthyroidism has been known to increase vasomotor activity and up-regulate numbers of adrenergic receptors, resulting in enhanced sympathoadrenal activity [ 8 , 9 ]. When we consider that the VA is a disease caused by the alteration and imbalance of vasomotor tone [ 10 ], we can assume that the thyroid hormone, which influences the sympathetic tone and vascular constriction/relaxation, is more likely to be related to the development and the prognosis of VA than to atherosclerotic ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic diseases such as hyperthyroidism and myeloproliferative disorders can cause an increase in the body's metabolic demand in turn leading to high cardiac output state [3]. Hyperthyroidism is characterized by increased activation of the thyroid gland causing excessive secretion of thyroid hormones, which in turn affects both cardiac and systemic tissues [11][12][13][14][15]. Cardiac effects lead to hypercontractility and increased heart rate, while increased systemic metabolism leads to increased cellular waste products and decreased systemic vascular resistance.…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…If left untreated, hypercontractility, tachycardia and volume overload can potentially lead to cardiac pathologies such as hypertrophy, cardiomyopathy and ultimately HF. Myeloproliferative disorders (increased production of abnormal red/ white blood cells or platelets) on the other hand, if left untreated can lead to increased cellular metabolism and high cell turnover resulting into a state of increased metabolic demands and low systemic vascular resistance [11][12][13][14][15].…”
Section: Metabolic Diseasesmentioning
confidence: 99%